Septal rhinoscleroma - Shoeib, Mohamed A. (Medknow Publication, 2010)
Rhinoscleroma is a chronic granulomatous condition of the nose and other structures of the upper respiratory tract. Infection by the bacterium Klebsiella rhinoscleromatis is said to be the cause. A female patient aged 45 years, presented with a past history of trauma to the nose and swelling on her nose since last 1 year. There was nasal asymmetry and internal nasal examination showed a septal swelling protruding to the right nasal cavity with hypertrophied nasal mucosa and inferior turbinate. Open tip rhinoplasty approach was used to excise the mass, which examined pathologically revealing a rhinoscleroma, fibrotic infiltrative stage.